Report of the IEA Workshop on Evaluating the Quality of Science, Rome, 10-11 December 2015 - CGIAR Independent Evaluation Arrangement (CGIAR Independent Evaluation Arrangement, 2015)
IEA organized a 1.5 day (10-11 December 2015) internal workshop to discuss approaches and experiences in assessing science quality, primarily through evaluations in the CGIAR. The overall purpose of the workshop was to consolidate and strengthen IEA’s approach to evaluating the quality of science in the CGIAR considering the evaluation framework, evidence used, interpretation of findings and lessons for users of evaluation. Given the experience accumulated through the recent evaluations, the workshop aimed at feeding into the broader ISPC–led discussion on QoS in the CGIAR, and for future research evaluation. Through its work, the IEA also aims at enhancing the conceptualization of QoS in the research for development framework at CGIAR centers and programs. The workshop was attended by approximately 15 participants, representing IEA and its evaluation teams (team leader and member), ISPC, Consortium Office, IDRC, a CRP scientist and a donor. Discussions focused on exploring a common definition and understanding of assessing the quality of science and research across CGIAR, and defining the scope, approach, and tools which can be used.